2000
DOI: 10.1097/00006534-200009040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient Satisfaction in Postmastectomy Breast Reconstruction

Abstract: In today's increasingly competitive health care marketplace, consumer satisfaction has become an important measure of quality. Furthermore, measures of satisfaction with treatment inteerventions are influential factors in determining patients' and payers' choices of health care. This study sought to evaluate satisfaction with postmastectomy breast reconstruction and to assess the effects of procedure type and timing on patient satisfaction. As part of the Michigan Breast Reconstruction Outcome Study, patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 17 publications
7
120
0
8
Order By: Relevance
“…28,31,32 The results obtained here confirm that satisfaction with Breast Reconstruction does not depend directly on women's age or educational level. 29 Nearly half of young Breast Cancer survivors expressed some regret five years after their treatment; 33 regret about Breast Reconstruction was also observed here in about half of the sample, in line with other studies. 31,32 Post-decisional regrets were observed more frequently in our study when the decision-making was not felt to be sufficiently proactive and in those who were less satisfied with their Breast Reconstruction.…”
Section: Iv-logisticsupporting
confidence: 91%
See 1 more Smart Citation
“…28,31,32 The results obtained here confirm that satisfaction with Breast Reconstruction does not depend directly on women's age or educational level. 29 Nearly half of young Breast Cancer survivors expressed some regret five years after their treatment; 33 regret about Breast Reconstruction was also observed here in about half of the sample, in line with other studies. 31,32 Post-decisional regrets were observed more frequently in our study when the decision-making was not felt to be sufficiently proactive and in those who were less satisfied with their Breast Reconstruction.…”
Section: Iv-logisticsupporting
confidence: 91%
“…Satisfaction with the plastic surgeon has been previously reported to predict greater satisfaction with Breast Reconstruction. 28 In previous studies on satisfaction with Breast Reconstruction, the role of various clinical variables was investigated, and women with autologous reconstruction were found to be more satisfied than those with implants, 29 which was confirmed by the present results. Two other variables analyzed in our study were found to be independently related to satisfaction: higher informationseeking profiles and lower health-related literacy.…”
Section: Iv-logisticsupporting
confidence: 85%
“…Different authors have considered the impact of implant versus autogenous tissue techniques and of immediate versus delayed reconstruction. [19][20][21][22] However, to our knowledge, few have attempted to evaluate the effect of more subtle treatment considerations, such as implant type, on patients' perceptions of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, which suggests that both preoperative and postoperative radiotherapy are important predictors of patient satisfaction, is consistent with other published reports. Numerous studies have shown that patients who undergo postmastectomy, implant-based reconstruction after the receipt of preoperative chest wall irradiation have a higher incidence of complications, including capsular contracture, 19,[24][25][26] and that the receipt of postmastectomy adjuvant radiotherapy is correlated with both the development of complications and increased patient dissatisfaction. [27][28][29][30] Thus, the determination of effect size herein allowed clinically meaningful comparisons to be made between the effects of a known entity (such as postmastectomy radiotherapy) versus other clinical variables (such as implant type) that may have an impact on patients' satisfaction with their reconstructed breasts.…”
Section: Discussionmentioning
confidence: 99%
“…The cosmetic advantages of reconstruction with prosthesis provide the patient a positive impact on psychosocial aspects, organ functionality, and quality of life 8,9 . They explain the increasing number of indications, even after the increased costs attributed to post-mastectomy reconstruction 10,11 .…”
Section: Introductionmentioning
confidence: 99%